Actual transaction behavior of Internet Banking Services among Iraqis customers using PLS approach - Alkafagi, Alaa Ahmed Chyad; Romli, Ruslan; Bahaudin, Ahmad Yusni; Alekam, Jamal Mohammed Esmail; Mohammad Salameh, Anas Abdelsattar (IJSRP.ORG, 2015)
The main purpose of this research is to identify the factors that encourage adopters to take up the Internet banking services in Iraq This paper is concerned with an empirical investigation of individual factors technology that could predict successful IBSA in Iraq through the applications of planned behavior theory (TPB).This study uses sampling units in a questionnaire survey data of 535 Iraqis public university employees as customers of internet banking services who were using it already.This study applied partial least squares structural equation modeling (PLS-SEM) as the major analysis technique as well as SPSS, since PLS-SEM is a relatively new analytical technique in construction.The findings of this study suggests that attitude and percived behavior control(PBC) have significant and positively influences IBSA, while Subjective norm (SN) is unsuported.Related to individual factors technology (IFT), in this study there are 5 constructs all of them (technology and Internet literacy, resistance to change, risk of technology,and anxiety of technology, and trust of technolology) supported with researcher expectation.